PENENTUAN KADAR BESI DAN SENG DENGAN MENGGUNAKAN METODA INDUCTIVELY COUPLED PLASMA- ATOMIC EMISSION SPECTROCOPY PADA AIR BAKU DI KOTA BATAM - Dartini Dartini; Sri Elfina (Politeknik ATI Padang, 2019)
Water is a natural resource needed to fulfill the livelihood of many people, so it needs to be protected so that it can be beneficial to the lives and lives of humans and other living things. Batam City is one of the cities in Riau Islands Province which has a type of soil that cannot store water properly so that it uses an artificial reservoir as a reservoir of rainwater. Due to waste from industrial, domestic and other activities that have a negative impact on water resources. Then testing the iron and zinc content of the reservoir water in the city of Batam was carried out. Metal Iron and Zinc are metals that are needed by organisms in relatively small amounts. Based on Government Regulation No. 82 of 2001 class 1, allowed Iron and Zinc levels of 0.3 mg/L and 0.05 mg/L. The method used in this test is Inductively Coupled Plasma - Atomic Emission Spectrocopy (ICP - AES), with the principle based on atomizing elements so that they emit light at certain wavelengths which can then be measured. From the test, it was found that the iron content in Duriangkang reservoir 0.2339 ppm, Sei Harapan reservoir 0.0299 ppm, Mukakuning reservoir 0.0292 ppm, Sei Nongsa reservoir 0.4168 ppm, Rempang reservoir 0.0001 ppm, Tembesi reservoir 0.0420 ppm, Sei Ladi reservoir 0.0588 ppm. Zinc content in Duriangkang reservoir is 0.0083 ppm, Sei Harapan reservoir is 0.0554 ppm, Mukakuning reservoir is 0.0083 ppm, Sei Nongsa reservoir is 0.0004 ppm, Rempang reservoir is 0.0083 ppm, Tembesi reservoir is 0.0083 ppm, Sei Ladi reservoir is 0.0211 ppm. This shows that the reservoir water has fulfilled the class 1 water quality requirements stipulated by Government Regulation No. 82 of 2001 except Sei Nongsa reservoir for the parameters of Iron (Fe) and Sei Harapan reservoir for Zinc (Zn) parameters.